RETROPERITONEAL NON-ORGAN LIPOSARCOMAS: THE MODERN CONCEPT - A. Yu. Volkov; S. N. Nered; L. N. Lyubchenko (Сибирский онкологический журнал, 2019)
Objective: to conduct a systematic literature review of the published studies on retroperitoneal non-organ liposarcomas.Material and Methods. A literature search was performed using Pubmed, Elibrary, COSMIC databases. The data of retrospective and prospective clinical trials were analyzed. Results. The article reviews contemporary data on epidemiology, classification, clinicalmorphological and molecular-genetic characteristics, as well as diagnosis and treatment of retroperitoneal non-organ liposarcomas. Conclusion. Retroperitoneal sarcomas account for about 13 % of all types of soft tissue sarcomas. Liposarcoma is the most common retroperitoneal mesenchymal tumor. Diagnosis and treatment of non-organ retroperitoneal liposarcoma remain challenging due to poor long-term treatment outcomes. As experience is gained with the diagnosis and treatment of retroperitoneal nonorganic liposarcomas, changes occur in the system of understanding the problem that determines the strategy for providing medical care in this category of patients. The article presents modern concept of retroperitoneal non-organ liposarcomas.